(untitled) (Journal of Applied Oral Science, 2021)
Glaze application on monolithic zirconia (Y-TZP) can be a practical approach to improve the mechanical properties of this material. Objective: Our study evaluated the effect of glazing side and mechanical cycling on the biaxial flexure strength (BFS) of a Y-TZP. Methodology: Eighty sintered Y-TZP discs (Ø:12 mm; thickness: 1.2 mm - ISO 6872) were produced and randomly assigned into eight groups (n=10), according to the factors “glazing side” (control – no glazing; GT – glaze on tensile side; GC – glaze on compression side; GTC – glaze on both sides) and “mechanical aging” (non-aged and aged, A – mechanical cycling: 1.2×106, 84 N, 3 Hz, under water at 37°C). Specimens were subjected to BFS test (1 mm/min; 1,000 Kgf load cell) and fractured surfaces were analyzed by stereomicroscopy and SEM. Hsueh’s rigorous solutions were used to estimate the stress at failure of glazed specimens. Two-way ANOVA, Tukey’s test (5%), and Weibull analysis were performed. Results: The “glazing side”, “mechanical aging” and the interaction of the factors were significant (p<0.05). Groups GC (1157.9±146.9 MPa), GT (1156.1±195.3 MPa), GTC (986.0±187.4 MPa) and GTC-A (1131.9±128.9 MPa) presented higher BFS than control groups (Tukey, 5%). Hsueh’s rigorous solutions showed that the maximum tensile stress was presented in the bottom of zirconia layer, at the zirconia/glaze interface. Weibull characteristic strength (σo) of the GC was higher than all groups (p<0.05), except to GT, GTC-A and GTC, which were similar among them. The fractography showed initiation of failures from zirconia the tensile side regardless of the side of glaze application and fatigue. Conclusion: Glazing zirconia applied on both tensile and compression sides improves the flexural strength of Y-TZP, regardless the mechanical aging.